2020
DOI: 10.1002/pon.5477
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing loneliness in cancer caregivers: A longitudinal study

Abstract: Objective: To describe levels of loneliness in cancer caregivers over a 6 month time period, and to examine factors that influence changes in loneliness in caregivers over time. Methods: Prospective, repeated measures design was utilized to examine levels of loneliness and factors that influence loneliness in 129 family caregivers of individuals undergoing cancer treatment at three time points over a 6 month period. Measures included: PROMIS global health and sleep disturbance; NIH Toolbox loneliness, selfeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
(72 reference statements)
1
10
0
Order By: Relevance
“…We also found that patients with lower education and those without adequate financial support perceived more barriers. These findings parallel similar findings in the literature 47,59. In our perspective, they highlight a critical prerequisite for interventions to first address barriers and then focus on dietary behavior change.…”
Section: Discussionsupporting
confidence: 89%
“…We also found that patients with lower education and those without adequate financial support perceived more barriers. These findings parallel similar findings in the literature 47,59. In our perspective, they highlight a critical prerequisite for interventions to first address barriers and then focus on dietary behavior change.…”
Section: Discussionsupporting
confidence: 89%
“…Also, the regression analysis may suffer from endogeneity bias that includes reverse causality and omitted confounders. The bidirectional relationship between social isolation profiles and caregiver burden is plausible (Ross et al, 2020). Also, unobserved caregiver characteristics, such as caregiver personality traits, may influence both loneliness (Buecker et al, 2020) and caregiver burden (Melo et al, 2011), leading to the spurious association between the two.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that among both women and men, participants who had three roles (i.e., working, childrearing, and caregiving to aging parents) had significantly less psychological distress than those who had fewer roles (Honda et al, 2015). Further, a recent longitudinal study also confirmed that caregivers who were in the paid labor force reported a lower level of loneliness than non-working caregivers (Ross et al, 2020). Workplace interaction and resources may provide a "protective shield" against the loneliness from family caregivers.…”
Section: Multiple Roles and Social Isolation Among The Middle-aged Generationmentioning
confidence: 93%